Tidal dynamics in the strong tidal current environment of the Uldolmok waterway, southwestern tip off the Korean peninsula - Kang, Sok Kuh; Jung, Kyung Tae; Yum, Ki-Dai; Lee, Kwang-Soo; Park, Jin-Soon; Kim, Eun Jin (Ocean science journal, 2012)
Uldolmok waterway, located between an island off the southwestern tip of Korean peninsula and mainland, is famous for its strong tidal current that has a maximum current of about 6.0m/s. A series of field observations along with numerical modeling have been carried out in order to understand the tidal dynamics in terms of the force balance along the whole waterway and the energy balance in the narrowest part of the waterway. First, analysis of the ADCP current and the tide level variation data reveals that the tidal dynamics along the total waterway (channel) is balanced dominantly between the pressure gradient and linear bottom frictional forces, with the phase lag of sea level difference for the semi-diurnal constituents leading the current phase about by 10°. Secondly, the result of the numerical modeling reveals that the tidal energy flux vector flows toward the narrowest section, indicating that there should be related nonlinear processes. Through the numerical model experiment with multi-components, the convergence of (M 2 + S 2 ) tidal energy flux of 6.68 × 10 7 Joule/s in the narrow area of the Uldolmok waterway is explained mainly by the energy consumption of 73% through the nonlinear generation of shallow water components and by the bottom frictional energy dissipation of 27%. This reveals that the remarkably strong nonlinear process dominates in the narrowest section of the Uldolmok waterway, compared with other areas, such as Yellow and East China Seas where the total M2 energy flux through the open boundary is balanced in terms of the bottom dissipation (Kang et al. 2003; Choi 1980).